Análisis de métodos de eficiencia energética para vivienda existente ubicada en la ciudad de Duitama (2022)
The objective of this degree work is to make a state of knowledge about the different energy efficiency methods that we can include in buildings, in addition to proposing a case to implement solar exploitation technologies in an existing house located in Duitama city. Considering the negative environmental impacts that have arisen from energy consumption during the building's life cycle at a global level, the use of zero energy is very useful, that is, the union of renewable energies and energy efficiency. A proposed case of use of solar energy will be analyzed, using Revit software as a tool, for the modeling and design of photovoltaic and sanitary hot water networks, where we can distinguish important parameters to be taken into account for the execution of the project, such as the amounts, budget, economic viability through future value, and environmental impact in terms of CO2 emission reductions in ton CO2/KW